Analysis of Factors Related to the Performance of Officers in Discovery of Lung TB Case - Rita Zulfadilah; Sugeng Eko Irianto; Achmad Djamil; Dian Utama Pratiwi Putri (GLOBAL HEALTH SCIENCE GROUP, 2020)
Tuberculosis is still a global health problem, especially in developing countries including Indonesia. The incidence of tuberculosis in Indonesia is 391 per 100,000 population and the death rate is 42 per 100,000 population. The purpose of this study was to determine factors related to the performance of officers in the discovery of pulmonary TB cases in Way Kanan District. This is a quantitative research with cross sectional design. Respondents in this study were doctors of puskesmas, laboratory officers, village midwives and posyandu cadres as many as 355 people. From the population, simple random sampling was used and the samples were taken by using lottery technique which involved 180 people for the sample. The questionnaires which were given to the respondents were used to measure knowledge, attitude, motivation, leadership, reward, and work design. For the result, univariate data analysis, bivariate using the Chi-Square Test and multivariate using a multiple logistic regression test were employed. The results of the study with statistical tests show there is a relationship of knowledge with performance (p = 0,000), there is a relationship between attitude and performance (p = 0,000), there is a relationship of motivation with performance (p = 0,000), there is a relationship of leadership with performance (p = 0.005), there is a reward relationship with performance (p = 0,000), there is a relationship between job design and performance (p = 0,000) and the most dominant variable is motivation (OR = 7,490). In conclusion there is a relationship between knowledge, attitude, leadership, motivation, reward and job design with performance.